Implementasi Smart Helmet Cabinet pada Penyimpanan Helm Berbasis Mobile QR Code - Abdahu, Muhammad Raymount; Ristian, Uray; Hasfani, Hirzen (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
The use of Smart Helmet Cabinet in helmet storage based on Mobile QR Code has been implemented as an innovative solution to overcome the problem of safe and efficient helmet storage. By utilizing QR Code technology, authentication on the system facilitates users in the process of helmet storage and retrieval, as well as ensuring storage security. In addition, several challenges such as the need for reliable access authentication and reduction of access delay are the main focus to improve the effectiveness and reliability of the system. This research discusses the implementation of the Smart Helmet Cabinet by highlighting the benefits as well as potential future developments in improving user experience and security of stored helmets. The ESP32-CAM is used to scan the QR Code to authenticate user access, while the ESP32 NodeMCU controls the relay to open the door of the locker. The test results show that the average delay time for adding locker access is about 4.73 seconds, while access authentication using QR Code takes about 5.99 seconds. The implemented Smart Helmet Cabinet system is able to determine which lockers are given access and identify users by using QR Code as access authentication on the lockers